Normal bilirubinemia downregulates the power spectral density of the θ and Δ rhythm, instead upregulates the β rhythm and sympatho-vagal balance in adults humans - Korda, Mykhaylo; Gozhenko, Anatoliy; Kuchma, Igor; Korda, Inna; Popadynets’, Oleksandr; Badiuk, Nataliya; Korolyshyn, Tetyana; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2022)
Background. Neonatal hyperbilirubinemia has been known to damage neural function. Our goal is to determine whether the neurotropic activity of normal bilirubinemia in adults is evident. Methods. The object of observation were 77 volunteers: 30 women and 47 men aged 49±13 (26 ÷ 76) years without clinical diagnosis. Testing was performed twice with an interval of 4 ÷ 10 days. We determined the plasma levels of the direct and free bilirubin, recorded EEG and HRV followed by analysis of correlations between parameters. Results. Significant downregulating effect of bilirubinemia was found on power spectrum density (PSD) theta and delta rhythm. In contrast, bilirubinemia has an upregulating effect on PSD beta rhythm and sympatho-vagal balance. The canonical correlation between direct & free bilirubin levels, on the one hand, and EEG & HRV parameters, on the other hand, is very strong: R=0,808; R2=0,654; χ2(80)=191; p<10-6 (n=154). A similar canonical correlation was found between individual changes in parameters: R=0,753; R2=0,568; χ2(48)=83; p=0,001 (n=74). Conclusion. Even normal bilirubinemia has an downregulating effect on mainly theta and delta rhythm-generating nuclei and vagal tone, while upregulating effects on sympathetic tone and beta rhythm-generating nuclei.